A preliminary analysis of land use change and its impacts on groundwater resources in Balamban, Cebu, Philippines using GIS - Bagarinao, Ricardo T. (Journal of Environmental Science and Management, 2003)
Groundwater is potentially affected when land use changes due to agricultural and industrial developments. As there are many cases of groundwater degradation due to changing land use patterns throughout the world, a preliminary examination of the interrelationship between land use change and groundwater resource viability is in order. The analysis could be enchanced through the use of geographic information system (GIS).